Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3920/wmj2015.1905
|View full text |Cite
|
Sign up to set email alerts
|

A mycotoxin-dedicated total diet study in the Netherlands in 2013: Part III – exposure and risk assessment

Abstract: In a mycotoxin-dedicated total diet study (mTDS) performed in the autumn and winter of 2013 in the Netherlands, 48 mycotoxins, including patulin, aflatoxins, ochratoxin A, fumonisins, zearalenone, trichothecenes, ergot alkaloids, Alternaria toxins, beauvericin and enniatins, were quantified. Analyses were performed in 88 composite samples representative for the consumption pattern of the Dutch population. This article presents the results of the exposure assessment and subsequent risk assessment of these mycot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 57 publications
2
35
0
1
Order By: Relevance
“…In der einen Studie fanden sich nur für Trichothecene (DON sowie T-2 und HT-2) Expositionen oberhalb der TDI-Werte, und zwar bei einem geringen Anteil der Erwachsenen, aber einem höheren Anteil der Kinder [48]. Die zweite Studie fand für "upper-bound"-Schätzungen zur Exposition Überschreitungen der tolerablen Aufnahme für Ochratoxin A in der Altersgruppe 7-69 Jahre, für die Summe T-2 und HT-2 bei Kindern (2-6 Jahre) sowie für Alternariol und AME in beiden Gruppen [49]. Während für Aflatoxin B1 der "margin of exposure" (s. Die sehr begrenzte Datenlage zur Toxizität der Alternaria-Toxine gestattet bislang keine volle Risikocharakterisierung.…”
Section: Total-diet-studienunclassified
“…In der einen Studie fanden sich nur für Trichothecene (DON sowie T-2 und HT-2) Expositionen oberhalb der TDI-Werte, und zwar bei einem geringen Anteil der Erwachsenen, aber einem höheren Anteil der Kinder [48]. Die zweite Studie fand für "upper-bound"-Schätzungen zur Exposition Überschreitungen der tolerablen Aufnahme für Ochratoxin A in der Altersgruppe 7-69 Jahre, für die Summe T-2 und HT-2 bei Kindern (2-6 Jahre) sowie für Alternariol und AME in beiden Gruppen [49]. Während für Aflatoxin B1 der "margin of exposure" (s. Die sehr begrenzte Datenlage zur Toxizität der Alternaria-Toxine gestattet bislang keine volle Risikocharakterisierung.…”
Section: Total-diet-studienunclassified
“…In 2013, a mycotoxin-dedicated total human diet study was performed in the Netherlands showing that the main contributors to DON exposure were bread and cookies and biscuits in in children aged 2-6 years and adults aged 7-69 years. In the latter group, beer and pasta also contribute to the exposure to DON (Sprong et al, 2016;Lopez et al, 2016). Eggs are, therefore, not seen as a major contributor to human DON intake.…”
Section: Mycotoxinsmentioning
confidence: 99%
“…TDSs were developed to estimate the exposure of populations to food contaminants, including mycotoxins. From the studies presented in Table 2, Sirot et al (2013) and Sprong et al (2016a) evaluated the exposure of French and Dutch populations, respectively, to mycotoxins.. According to Lee et al (2015), countries as Australia, France, Korea and China had developed their country-specific TDSs including mycotoxins but all countries are encouraged to conduct total diet studies to assess the safety and nutritional quality of diet of their population since TDS is not only a costeffective tool but also a realistic tool for risk assessment of chemicals in foods.…”
Section: Worldwide Exposure Assessment Of Co-occurring Mycotoxins In mentioning
confidence: 99%
“…(Sirot et al, 2013;Sprong et al, 2016b). For the exposure assessment studies, food consumption data were mainly obtained from national food consumption surveys, including different data collection methodologies, namely 1-day (Cressey and Reeve, 2013;Han et al, 2014), 2-day (De Boevre et al, 2013;Sprong et al, 2016a;Van de Perre et al, 2015) and 3-day 24-hour recalls (Zhao et al, 2015), 3-day food diary and 7-day food diary (Sirot et al, 2013), all reported in Table 2.…”
Section: Worldwide Exposure Assessment Of Co-occurring Mycotoxins In mentioning
confidence: 99%